2022
DOI: 10.21272/mmi.2022.3-08
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sustainability Awareness in Uzbekistan

Abstract: In the frame of this article, the authors maintained that natural resources and environmental conditions are the basis of material production and the life of the population. Systematization of the scientific sources on sustainable development indicated that the state of the environment and the quality level of resource use, protection, and reproduction largely determine the rates of economic growth and production efficiency. The relevance of this scientific problem decision is that at the present stage of econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Given this, our findings also found that digital transformation significantly contributes to firms' sustainable performance. The digital transformation is essential for upgrading and improving the firm's sustainable performance [ 100 ]. It also empowers the firms to broaden their business model innovations.…”
Section: Discussionmentioning
confidence: 99%
“…Given this, our findings also found that digital transformation significantly contributes to firms' sustainable performance. The digital transformation is essential for upgrading and improving the firm's sustainable performance [ 100 ]. It also empowers the firms to broaden their business model innovations.…”
Section: Discussionmentioning
confidence: 99%
“…Business model innovation plays a critical role in leveraging digitalization to unlock these performance benefits. By reimagining and reconfiguring their business models to align with digital opportunities, enterprises can maximize the transformative potential of digital technologies and achieve sustainable growth [38][39][40][41][42][43][44][45].…”
Section: Digital Capabilities Affect Enterprise Performancementioning
confidence: 99%